APLIKASI PREDIKSI DALAM PENENTUAN JUMLAH PRODUKSI AIR MINUM ADENI PAMEKASAN DENGAN MENGGUNAKAN METODE FUZZY MAMDANI - Alvian Hidayatullah (Universitas Madura, 2022)
Uncertainty was a problem that can be found in the daily life, including when make a decision. In case when trying to determine the amount of production number, fuzzy logic concept is very effective because it can solves problem that contain uncertainty, partial truth and ambiguous. One of the fuzzy method that can be use to solve that problem was Fuzzy Inference System Method. Fuzzy Inference System Method that being used in this minithesis is Fuzzy Mamdani Method and software that being used is Visual Basic 6.0 with Microsoft Acces database. The results from Fuzzy Mamdani Method implementation will give a solution about the optimal amount that need to produced.Key Word : Fuzzy Inference Sistem, Mamdani Method, Determining Production Amount.